Patch quality and habitat fragmentation shape the foraging patterns of a specialist folivore. (17th July 2022) - Crowther, Mathew S; Rus, Adrian I; Mella, Valentina S A; Krockenberger, Mark B; Lindsay, Jasmine; Moore, Ben D; McArthur, Clare
Abstract: Research on use of foraging patches has focused on why herbivores visit or quit patches, yet little is known about visits to patches over time. Food quality, as reflected by higher nutritional quality and lower plant defenses, and physical patch characteristics, which offer protection from predators and weather, affect patch use and hence should influence their revisitation. Due to the potentially high costs of moving between patches, fragmented habitats are predicted to complicate foraging decisions of many animals. We aimed to determine how food quality, shelter availability and habitat fragmentation influence tree reuse by a specialist folivore, the koala, in a fragmented agricultural landscape. We GPS-tracked 23 koalas in northern New South Wales, Australia and collated number of revisits, average residence time, and average time-to-return to each tree. We measured tree characteristics including food quality (foliar nitrogen and toxic formylated phloroglucinol compounds, FPCs concentrations), tree size, and tree connectedness. We also modeled the costs of locomotion between trees. Koalas re-visited isolated trees with high leaf nitrogen disproportionately often. They spent longer time in trees with high leaf nitrogen, and in large trees used for shelter. They took longer to return to trees with low leaf nitrogen. Tree connectivity reduced travel costs between patches, being either individual or groups of trees. FPC levels had no detectable effect on patch revisitation. We conclude that food quality and shelter drive koala tree re-visits. Scattered, isolated trees with nutrient-rich leaves are valuable resource patches for koalas despite movement costs to reach them. Abstract : We GPS-tracked Australia's iconic koalas within a fragmented agricultural landscape to determine why they would return to the same trees or groups of trees. We found that they selected trees with high nitrogen, and larger trees that provided shelter from the heat. This often involved moving large distances across a hostile cleared landscape. Hence, scattered trees on farms, especially when the trees are of high quality, are essential for arboreal animals.